Comparison of Treatment Outcomes for Tennis Elbow: Corticosteroid Injection and Casting vs. Acupuncture and Physiotherapy - Sina Heydari; Aboubakr Jafarnezhad; Reza Faryabi; Rasoul Raesi; Mahya Goroohi; Akbar Mehralizade; Fatemeh Amiri Ghanatsaman; Salman Daneshi (Journal of Advanced Biomedical Sciences, 2024)
Background & Objectivs: Today, despite the existence of numerous treatments for tennis elbow, the search for more effective methods continues due to the limited efficacy of these existing approaches. This study aimed to compare the results of tennis elbow treatment in two groups: patients receiving corticosteroid injection and casting, and patients receiving acupuncture and physiotherapy. Materials & Methods: This quasi-experimental study, conducted in Jiroft in 2021, investigated the effectiveness of different treatment approaches for tennis elbow. Fifty patients diagnosed with tennis elbow were randomly divided into two groups of 25 each. One group received a combination of corticosteroids and casts, while the other group received acupuncture and physiotherapy.  A pain line was used to assess pain levels based on VAS criteria. Data were analyzed using SPSS-26 statistical software, employing Chi-square, Fisher's Exact, Mann-Whitney, one-way ANOVA, Kruskal-Wallis, and Kolmogorov-Smirnov tests. Results: The majority of patients were female (66%) and housewives (46%).  There was a significant difference in pain outcomes between the two groups: physiotherapy alone and physiotherapy combined with corticosteroids and casts. This difference was observed across various conditions (pain at rest, pain during activity, and amount of pain evoked during activity) (p <0.05). In simpler terms, corticosteroids and casts were more effective in reducing pain from tennis elbow compared to acupuncture and physiotherapy.  Additionally, corticosteroids and casts had a greater effect on hand movement (supination, pronation, extension, and flexion) compared to acupuncture and physiotherapy. Conclusion: Our findings indicate that treatment of tennis elbow with a combination of corticosteroid injection and casting is more effective than acupuncture or physiotherapy alone. Corticosteroid injections themselves are also an effective way to relieve tennis elbow pain.